2013
DOI: 10.2478/v10222-012-0079-z
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Nutrient Composition and Protein Quality of Potential Complementary Foods Formulated from the Combination of Fermented Popcorn, African Locust and Bambara Groundnut Seed Flour

Abstract: Key words: popcorn-based complementary foods, amino acid profi le, nutritional qualityThe aims of this study are to produce and evaluate nutritional quality of complementary foods using popcorn, bambara groundnut and African locust beans.The food materials were fermented, oven dried, milled and sieved into fl our. The fl ours were mixed as follows: fermented popcorn-African locust bean (FPA) (70% popcorn, 30% African locust bean), fermented popcorn-bambara groundnut (FPB) (70% popcorn, 30% bambara groundnut) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
81
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(97 citation statements)
references
References 29 publications
12
81
4
Order By: Relevance
“…From Figure (Supplementary Table 4), rats fed on FMSM‐based IWFs retained and utilized their dietary Ca identically with those fed on the commercial foods, while the P retention and subsequent utilization by rats fed on the formulated IWFs except IWFs 1 and 5) compared favorably with those fed on the commercial foods. This implies that rat fed on the laboratory‐formulated foods would support the growth of bone and teeth formation similar to that of the commercial foods (Ijarotimi & Keshinro, ).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…From Figure (Supplementary Table 4), rats fed on FMSM‐based IWFs retained and utilized their dietary Ca identically with those fed on the commercial foods, while the P retention and subsequent utilization by rats fed on the formulated IWFs except IWFs 1 and 5) compared favorably with those fed on the commercial foods. This implies that rat fed on the laboratory‐formulated foods would support the growth of bone and teeth formation similar to that of the commercial foods (Ijarotimi & Keshinro, ).…”
Section: Resultsmentioning
confidence: 91%
“…According to FAO (), food insecurity refers to the consequences of inadequate consumption of nutritious food, considering the physiological use of food by the body as being within the domain of nutrition and health. For preschool children, inadequate breast milk of the mother is often supplemented with commercial infant weaning foods (IWFs), which are expensive and out of reach of the low‐income population in many parts of the developing countries (Agbede & Aletor, , Ijarotimi & Keshinro, ). Thus, the need to include in the menu of preschool children and other protein vulnerable groups foods made from local ingredients is imperative for these countries (Agbede & Aletor, ; Solomon, ).…”
Section: Introductionmentioning
confidence: 99%
“…Enrichment of cereal-based food with other protein source such as legumes, oilseeds etc, have received considerable attentions since investigations have revealed that cereals are deficient in lysine and tryptophan but have sufficient sulphurcontaining amino acids which are limiting in legumes [7]. In view of these nutritional challenges, quite a number of studies have investigated ways of formulating quality complementary foods through a combination of available plant based foods to meet the nutritional demands of infants of weaning age [6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Journal Of Food Chemistry and Nanotechnology | Volume 3 Issumentioning
confidence: 99%
“…The fibre content of the developed samples was less than the recommended value of less than 5% specified by the FSSAI (2011) [28]. Weaning food with low fibre content is very important as this would enable children to consume food that is more nutrient-dense and to meet the daily energy and other vital nutrient requirements [31]. Emphasis is placed on the importance of low fibre in weaning food because the gastrointestinal system of the infants may not be well developed to handle diet high in fibre content as this has been reported to impair protein and mineral digestion and absorption in human subjects [14].…”
Section: Discussionmentioning
confidence: 99%